An inner-field uniform pressure actuator with high performance and its application to titanium bipolar plate forming. (August 2020) - Wu, Zelin; Cao, Quanliang; Fu, Junyu; Li, Zhangzhe; Wan, Yong; Chen, Qi; Li, Liang; Han, Xiaotao
Abstract: Uniform pressure actuators (UPAs) have unique advantages for electromagnetic forming, and they have excellent prospects in specific applications. The typical structure of conventional UPAs consists of an internal coil and an external conductive channel; this leads to certain limitations such as poor electrical contact and low coil strength. In the present study, in order to resolve these shortcomings, a new type of UPA is proposed, in which the induced circuit consists of a conductive channel and a workpiece that is placed inside a spiral coil. Benefitting from the innovation of the special structure, the proposed UPA can improve the electrical contact by producing a squeezing force between the conductive channel and workpiece during the forming process. Moreover, it provides an open reinforced environment for increasing the coil strength without affecting the forming efficiency. Numerical and experimental studies demonstrate that forming efficiency of the proposed UPA is higher than that of the conventional UPA. Based on these advantages and the new proposed uniform-velocity method, the proposed UPA is applied to fabricate a fuel cell titanium bipolar plate in a single discharge process. Graphical abstract: Image 1 Highlights: Inner-field uniform pressure actuator (UPA) solved arcing issues by squeezing force. The coil strength of Inner-field UPA can be improved by open reinforcement space. The Inner-field UPA has higher forming efficiency than the conventional UPA. The fully coupled finite element models of two types of UPAs are first established. The complex titanium bipolar plate was formed by the new uniform-velocity method.